Cost evaluations of radiotherapy: What do we know? An ESTRO-HERO analysis. Issue 3 (December 2016) - Defourny, Noémie; Dunscombe, Peter; Perrier, Lionel; Grau, Cai; Lievens, Yolande
Abstract: Although economic evidence is becoming mandatory to support health care decision-making, challenges remain in generating high quality cost data, especially for complex and rapidly evolving treatment modalities, such as radiotherapy. The overall aim of this systematic literature review was to critically analyse the type and quality of radiotherapy cost information available in cost calculation studies, from the health care provider's perspective, published since 1981. A selection process, based on strict and explicit criteria, yielded 52 articles. In spite of meeting our criteria these studies displayed large heterogeneity in scope, costing method, inputs and outputs. The limited use of conventional costing methodologies along with insufficient information on resource inputs hampered comparability across studies. A consistent picture of radiotherapy costs, based on methodologically sound costing studies, has yet to emerge. These results call for developing a well-defined and generally accepted cost methodology for performing economic evaluation studies in radiotherapy.